Essential surgical practice higher surgical training in general surgery - Cuschieri, A. (Alfred); Hanna, George B. (CRC Press/Taylor & Francis Group, 2015)
Significant changes in surgical training have occurred over the past decade, with the inevitable progress towards specialization in the various surgical specialties. The current edition of Essential Surgical Practice: Higher Surgical Training in General Surgery reflects these latest developments with a new structure that accurately mirrors current surgical training.